Salivary lubricity (ex vivo) enhances upon moderate exercise: A pilot study. (August 2020) - Hopkins, Mark; Boesch, Christine; Lansdall, Matthew; Mullen, Conor; Mighell, Alan; Pavitt, Sue; Sarkar, Anwesha
Highlights: Moderate intensity exercise leads to enhanced lubrication performance of saliva. Such enhanced lubrication performance was sustained after 60 min of rest. Protein content and α -amylase activity in saliva was elevated post-exercise. Protein content and α -amylase activity returned to baseline with an hour. Effects of exercise on salivary mucin (MUC5B) content was not observed. Abstract: Objective: This study sought to examine the effects of moderate intensity exercise on lubrication performance of saliva. We hypothesized that exercise would result in enhanced salivary lubricity by direct sympathetic stimulation of the salivary proteins. Study design: In total, 11 healthy young pre-menopausal female participants (mean age: 24.4 ± 1.8 years, BMI: 22.1 ± 1.9 kg/m 2 ) were included in a within-subjects repeated measures experimental design. Unstimulated whole saliva was collected at rest (S0 ), immediately after 45 min of moderate intensity cycling at ∼70 % maximum heart rate (mean: 133.4 ± 0.8 bpm) or time-match quiet rest (S1 ), and after a 60 min of recovery period (S2 ). Ex vivo salivary lubricity were measured using soft tribology. Total protein content, mucin (MUC5B) concentration, and α -amylase activity were determined. Results: Tribology results revealed that moderate intensity exercise resulted in enhanced lubricity of saliva with an order-of-magnitude lower friction coefficients in the boundary regime at S1 and S2, with frictional forces being significantly lower at S1 ( p < 0.001 ) and S2 ( p < 0.001 ) as compared to the Control procedure. Total protein and α -amylase secretion also increased in the Exercise procedure at S1 ( p < 0.05 ), but concentrations returned to baseline levels at S2 . Conclusions: Moderate intensity exercise leads to an increase in α -amylase and total protein secretion resulting in enhanced lubrication performance of the saliva. However, the lubrication performance was not related to MUC5B content, suggesting the role of other proteinaceous species acting as lubricants. This proof-of-concept study serves as the first step to design exercise interventions in populations with dry mouth conditions.